The Bloomsbury handbook of reading perspectives and practices - Marshall, Bethan 1958-; Manuel, Jackie; Pasternak, Donna L.; Rowsell, Jennifer 1969- (Bloomsbury Academic, 2020)
"The Bloomsbury Handbook of Reading Perspectives and Practices focuses on the experiences of reading from a young age to maturity and the different ways reading is encountered, in other words the processes involved as well as the outcomes. The international group of experts, both within teaching and academia, focus on reading in school: how is it taught? What is taught? How is it assessed? Controversial issues are explored: the acquisition of phonics; teaching the canon, including or ignoring digital texts; the advent of standards-based tests. The contributions also consider people's biographies of reading, their memories of reading in class and their current views on literature. Together, this well-edited volume provides a more complete view of reading than is currently on offer, exploring all aspects of what it means to be literate and how we define being literate."
Includes bibliographical references and index
Keywords: Educational: English language: readers & reading schemes / bicssc; Books and reading / Social aspects; Reading / Study and teaching (Basic education)